Gut microbiota composition reflects disease progression, severity and outcome, and dysfunctional immune responses in patients with hypertensive intracerebral hemorrhage - Luo, Jielian; Chen, Yang; Tang, Guanghai; Li, Zhuo; Yang, Xiaobo; Shang, Xiaoxiao; Huang, Tao; Huang, Gan; Wang, Lixin; Han, Yun; Zhou, Yuexiang; Wang, Chuyang; et al. (Frontiers in Immunology, 2022)
Objective In this study, we aimed to explore the alterations in gut microbiota composition and cytokine responses related to disease progression, severity, and outcomes in patients with hypertensive intracerebral hemorrhage (ICH). Methods Fecal microbiota communities of 64 patients with ICH, 46 coronary heart disease controls, and 23 healthy controls were measured by sequencing the V3-V4 region of the 16S ribosomal RNA (16S rRNA) gene. Serum concentrations of a broad spectrum of cytokines were examined by liquid chips and ELISA. Relationships between clinical phenotypes, microbiotas, and cytokine responses were analyzed in the group with ICH and stroke-associated pneumonia (SAP), the major complication of ICH. Results In comparison with the control groups, the gut microbiota of the patients with ICH had increased microbial richness and diversity, an expanded spectrum of facultative anaerobes and opportunistic pathogens, and depletion of anaerobes. Enterococcus enrichment and Prevotella depletion were more significant in the ICH group and were associated with the severity and functional outcome of ICH. Furthermore, Enterococcus enrichment and Prevotella depletion were also noted in the SAP group in contrast to the non-SAP group. Enterococci were also promising factors in the prognosis of ICH. The onset of ICH induced massive, rapid activation of the peripheral immune system. There were 12 cytokines (Eotaxin, GM-CSF, IL-8, IL-9, IL-10, IL-12p70, IL-15, IL-23, IL-1RA, IP-10, RANTES, and TNF-α) changed significantly with prolongation of ICH, and the Th2 responses correlated with the 90-day outcomes. Cytokines TNF-α, IP-10, IL-1RA, IL-8, IL-18, and MIP-1β in SAP group significantly differed from non-SAP group. Among these cytokines, only IP-10 levels decreased in the SAP group. Enterococcus was positively associated with IL-1RA and negatively associated with IP-10, while Prevotella was inversely associated in both the ICH and SAP groups. Conclusion This study revealed that gut dysbiosis with enriched Enterococcus and depleted Prevotella increased the risk of ICH and subsequently SAP. The altered gut microbiota composition and serum cytokine profiles are potential biomarkers that reflect the inciting physiologic insult/stress involved with ICH.